Характеристики і параметри плазми перенапруженого наносекундного розряду в повітрі з малими домішками парів перехідних металів - Shuaibov, O. K.; Minya, O. Y.; Chuchman, M. P.; Malinina, A. O.; Malinin, O. M.; Danilo, V. V.; Gomoki, Z. T. (Publishing house "Academperiodika", 2018)
Parameters of the nanosecond overvoltage discharge plasma in an air gap of (1÷5) × 10−3 m between the electrodes, which contains the vapor of an electrode material (Zn, Cu, Fe) injected into plasma due to the ectonic mechanism, have been studied. The dependences of those parameters on the ratio E/N between the electric field strength E and the particle concentration N in the discharge are calculated for the “air–copper vapor” system, by using the numerical simulation method.